2016
DOI: 10.1016/j.micromeso.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Binary supercritical CO 2 solvent mixtures for the synthesis of 3D metal-organic frameworks

Abstract: Efficient and sustainable synthesis of MOFs, as nano or microcrystalline powder, is crucial for the development of new applications for these compounds. For this purpose, the synthesis of Zn 2+ , Cu 2+ and Fe 3+-based MOFs was attempted in this study by using a binary medium consisting of supercritical CO2 mixed with an ionic liquid (emimBF4 or emimBr). In comparison with conventional solvothermal and ionothermal synthesis, MOFs were herein obtained under mild reaction conditions, i.e. 200 bar and 65 ºC, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Indeed, using ZnO and H MeIm that had been thoroughly desiccated enabled formation of pure ZIF-8 after 5 min in scCO 2 at 65 °C and 130 bar (Figure g). Such fast reactivity of ZnO in scCO 2 , on a gram scale, in the absence of additives or mechanical force, is unprecedented and contrasts previous reports citing the insolubility of metal precursors in pure scCO 2 as a limitation to its use for MOF synthesis. Importantly, scCO 2 appears to be critical for the reaction, as it was shown that thermal reactivity of ZnO with H MeIm is negligible below 120 °C, and even then takes 24 h to complete . It is also notable that activators or catalytic additives, required for most solution and solid-state syntheses of ZIFs from ZnO, were not needed in scCO 2 (see Supporting Information for a more detailed assessment of the Green Chemistry metrics of methods for MOF synthesis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, using ZnO and H MeIm that had been thoroughly desiccated enabled formation of pure ZIF-8 after 5 min in scCO 2 at 65 °C and 130 bar (Figure g). Such fast reactivity of ZnO in scCO 2 , on a gram scale, in the absence of additives or mechanical force, is unprecedented and contrasts previous reports citing the insolubility of metal precursors in pure scCO 2 as a limitation to its use for MOF synthesis. Importantly, scCO 2 appears to be critical for the reaction, as it was shown that thermal reactivity of ZnO with H MeIm is negligible below 120 °C, and even then takes 24 h to complete . It is also notable that activators or catalytic additives, required for most solution and solid-state syntheses of ZIFs from ZnO, were not needed in scCO 2 (see Supporting Information for a more detailed assessment of the Green Chemistry metrics of methods for MOF synthesis).…”
Section: Resultsmentioning
confidence: 99%
“…Herein described reactivity is especially surprising as the recent explorations of scCO 2 as a medium for making metal–organic materials have established the inability to use conventional metal salts as precursors. As a result, the use of supercritical CO 2 in making MOFs and coordination polymers has relied on solubilizing additives, such as ionic liquids, or specialized reagents such as zinc hexafluoroacetylacetonate, that enable solubilization of metal species. …”
Section: Introductionmentioning
confidence: 99%
“…Compressed or supercritical carbon dioxide has been widely applied to a range of MOF processing steps including crystallisation [100][101][102], impregnation [103], dispersion [104], drying [105], and activation [106,107]. Formation of highly porous materials will generally benefit from the use of supercritical drying (typically scCO 2 ), with the low viscosity and high diffusivity of supercritical fluids being recognised as being especially vital for activation of large pores, to avoid pore collapse in MOFs during solvent removal [108].…”
Section: Compressed or Supercritical Carbon Dioxide Methodsmentioning
confidence: 99%
“…For more than ten years now, alternative methods have been developed and evolved in agreement with the green chemistry concept. The aims of these methods were to 1) develop Lewis acid catalyzed reactions in supercritical fluids, such as supercritical CO 2 or supercritical water; and 2) create an alternative reaction medium to volatile organic solvent by using ionic liquids . The great advantages of using these liquids are their nonflammability, high chemical and thermal stability, conductivity and polarity, negligible vapor pressures, ability to solvate solutes, miscibility with organic solvents and water, and their recycling processes.…”
Section: Reactions Catalyzed By Conventional Homogenous Lewis Acidsmentioning
confidence: 99%